Developing Entrepreneurial Values of Principals: A Qualitative Case Study in a Secondary School - Pratiwi, Sri Nurabdiah (Indonesian Journal Education, 2025)
Principals in Indonesian secondary schools are mandated to embed entrepreneurial character in daily learning, yet practical, evidence-based models remain limited. This qualitative case study at MTs Aisyiyah, North Sumatra, explores how a principal’s entrepreneurial competence is operationalised and how it affects the school community. Data were collected through semi-structured interviews with one principal, eight teachers and twenty students, and through non-participant observation of project-based activities that transform unused materials into marketable products. Thematic analysis revealed three key findings. First, the principal strategically integrated 17 entrepreneurial values—most visibly creativity, independence, discipline and responsibility—into both the formal curriculum and extracurricular programmes centred on up-cycling. Second, sustained teacher involvement in mentoring and assessment proved critical to reinforcing these values and modelling entrepreneurial behaviour. Third, the programme generated tangible shifts in school culture: students demonstrated greater problem-solving autonomy, while teachers reported heightened innovation in lesson design. The study concludes that visionary, risk-embracing leadership coupled with consistent teacher support can convert entrepreneurship policy into a living, school-wide practice, offering a replicable pathway for character-based education in similar contexts.